IMPLEMENTASI PENDIDIKAN KESELAMATAN DAN KESEHATAN KERJA (K3) PADA UMKM BAWANG GORENG DI DESA BANYUANYAR LOR - Tiyas, Mutiah Cahyaning Tiyas; Indiarti, Kinanti Indiarti; Laily Oktavia Ningrum; Ubaidila; Robiatul Adawiyah (As-Sulthan Journal of Education, 2025)
This research aims to implement the procurement of occupational health and safety (OHS) facilities in small and medium enterprises (SMEs) producing fried onions in Banyuanyar Lor Village. The issue raised is the high risk of workplace accidents due to unsafe electrical installations, such as tangled, unprotected cables. The research method used is a qualitative approach in Community Service (PKM), involving direct observation and in-depth interviews with informants, including SME owners, workers, and related parties such as the labor department. The program includes an initial assessment to identify potential hazards, followed by training and education on workplace safety, risk identification, and preventive measures that can be taken. The results show that providing facilities and raising awareness about the importance of OHS among SME operators can reduce workplace accident risks and increase productivity. The discussion emphasizes the need for support from the government and related agencies in providing technical and financial assistance, as well as more intensive OHS outreach programs. Thus, this research is expected to contribute significantly to creating a safer and healthier working environment for workers in the SME sector.